2007
DOI: 10.1016/j.bbr.2006.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination learning and reversal of the conditioned eyeblink reflex in a rodent model of autism

Abstract: Offspring of rats exposed to valproic acid (VPA) on Gestational Day (GD) 12 have been advocated as a rodent model of autism because they show neuron loss in brainstem nuclei and the cerebellum resembling that seen in human autistic cases [20,37]. Studies of autistic children have reported alterations in acquisition of classical eyeblink conditioning [40] and in reversal of instrumental discrimination learning [9]. Acquisition of discriminative eyeblink conditioning depends on known brainstem-cerebellar circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 54 publications
(127 reference statements)
6
25
0
Order By: Relevance
“…The most remarkable finding in the present study was impaired reward-based reversal learning in the cerebellar lesion group, a deficit which has previously been documented in rodents with cerebellar damage [50]. The present data extend previous findings which related reward-based reversal learning to the ventral PFC [10] and the ventral [9] and dorsal striatum [8].…”
Section: Impairment Of Reward-based Reversal Learningsupporting
confidence: 90%
“…The most remarkable finding in the present study was impaired reward-based reversal learning in the cerebellar lesion group, a deficit which has previously been documented in rodents with cerebellar damage [50]. The present data extend previous findings which related reward-based reversal learning to the ventral PFC [10] and the ventral [9] and dorsal striatum [8].…”
Section: Impairment Of Reward-based Reversal Learningsupporting
confidence: 90%
“…Acquisition of discriminative eyeblink conditioning depends on the brainstem-cerebellar circuitry whereas reversal learning involves long-range interactions between the cerebellum and the hippocampus and prefrontal cortex. VPA exposed rats exhibited faster eyeblink conditioning, in line with the findings in autistic children (Stanton et al, 2007). In a series of cognitive tests, prenatally VPA-treated rats had changes in the delayed non-match-to-sample task, novel object recognition, activity box, and Whishaw tray reaching task.…”
Section: Animal Models Of Cerebellum Dysfunctionsupporting
confidence: 86%
“…Those results confirm existence of similarities between the observed pattern of aberrations in VPA rats and features of disturbed behaviour in autistic patients. Noteworthy, VPA rats express a very specific pattern of aberration in eye-blink conditioning test (Murawski et al, 2009;Stanton et al, 2007), which is similar to that reported by Sears and colleagues (1994) in autistic patients, i.e., normal basic sensory and motor function, but exaggerated amplitude of conditioned blinks, and altered timing of conditioned blinks. One difference between children with autism and the VPA-exposed rats was that the animals did not display a higher rate of acquisition of conditioned responses.…”
Section: Behavioural Similarities To Autismsupporting
confidence: 87%